2019
DOI: 10.1370/afm.2389
|View full text |Cite
|
Sign up to set email alerts
|

Opioid and Substance Use Disorder and Receipt of Treatment Among Parents Living With Children in the United States, 2015-2017

Abstract: PURPOSE Little is known about the prevalence of opioid use disorder (OUD) among parents who are living with children and their receipt of treatment, which could reduce the harmful effects of OUD on families. METHODS We used 2015-2017 cross-sectional national survey data to estimate prevalence and treatment of opioid use disorder and other substance use disorders (SUD) among parents living with children. RESULTS An estimated 623,000 parents with opioid use disorder are living with children, and less than one-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…24 There are some indications that treatment with buprenorphine in general medical settings may have also increased in tandem with these funding changes. 51,53…”
Section: Discussionmentioning
confidence: 99%
“…24 There are some indications that treatment with buprenorphine in general medical settings may have also increased in tandem with these funding changes. 51,53…”
Section: Discussionmentioning
confidence: 99%
“…prior authorization) and coverage for substance use services varies across states, all state Medicaid programs include coverage for buprenorphine (Grogan et al, 2016). Medicaid spending on prescription medications used to treat OUD has increased substantially in recent years, to nearly a billion dollars in 2016 (Clemans-Cope, Epstein, & Kenney, 2017). With growing demand and investment in medications for OUD treatment, understanding factors related to retention within the Medicaid program is critical to develop practices and policies that improve outcomes and maximize resources.…”
Section: Introductionmentioning
confidence: 99%
“…67 Second, research on Medicaid-covered utilization of buprenorphine has also shown greater increases in the number of prescriptions and the dollars spent in Medicaid expansion states. 68,69 Thus, while physicians in Medicaid expansion states were not more likely to accept this form of payment, the Medicaid expansion remains important for broader questions of buprenorphine treatment supply and access to treatment.…”
Section: Discussionmentioning
confidence: 99%